2017
DOI: 10.1016/j.chom.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

CATALASE2 Coordinates SA-Mediated Repression of Both Auxin Accumulation and JA Biosynthesis in Plant Defenses

Abstract: Plants defend against pathogen attack by modulating auxin signaling and activating the salicylic acid (SA) and jasmonic acid (JA) signaling pathways. SA and JA act antagonistically in resistance to specific pathogen types, yet how plants coordinate these phytohormones remains elusive. Here we report that biotrophic-pathogen-induced SA accumulation dampens both auxin and JA synthesis by inhibiting CATALASE2 (CAT2) activity in the model plant Arabidopsis. SA suppression of CAT2 results in increased HO levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
228
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(238 citation statements)
references
References 34 publications
8
228
1
1
Order By: Relevance
“…The full extent to which catalase activity contributes to plant immune responses has only recently come to light. Catalases have previously been reported to bind SA, and a recent study showed that SA-induced suppression of CAT2 activity increased H 2 O 2 levels upon pathogen infection (21). Here we show that additionally, during oxidative stress and pathogen infection, CAT2 activity is regulated by NRX1.…”
Section: Discussionsupporting
confidence: 64%
“…The full extent to which catalase activity contributes to plant immune responses has only recently come to light. Catalases have previously been reported to bind SA, and a recent study showed that SA-induced suppression of CAT2 activity increased H 2 O 2 levels upon pathogen infection (21). Here we show that additionally, during oxidative stress and pathogen infection, CAT2 activity is regulated by NRX1.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, the crosstalk between defense and growth is, at least partially, redox-mediated. The catalase mutant cat2 , which is under constitutive oxidative stress, exhibits dwarfism but has increased resistance against biotrophic pathogens [7476]. It was found that SA directly binds to plant catalases to inhibit their activity [77,78].…”
Section: Balancing Growth and Immunity: Combined Influence Of The mentioning
confidence: 99%
“…It was found that SA directly binds to plant catalases to inhibit their activity [77,78]. In A. thaliana , the inhibition of CAT2 activity by SA leads to an increase in H 2 O 2 and subsequent sulfenylation (oxidation of a thiol -SH into sulfenic acid -SOH) of tryptophan synthetase β subunit 1 (TSB1) [76]. Reduced levels of tryptophan, the auxin precursor, cause reduced growth, but stronger immunity.…”
Section: Balancing Growth and Immunity: Combined Influence Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, CAT3 and ACX4 activity and transcripts are both elevated by carbon-starvation (Contento and Bassham, 2010). Moreover, cat2 mutants display decreased ACX activity Yuan et al, 2017), and overexpressing ACX3 rescues cat2 seedling growth defects . The finding that ACX activity is limiting for cat2 growth implies that ACX enzymes suffer damage when catalase is dysfunctional.…”
Section: Reactive Oxygen and Nitrogen Species: Not Just For Cell Deathmentioning
confidence: 99%